Fixation alters the physical properties of tumor tissue that regulate nanomedicine transport - John D. Martin; Fotios Mpekris; Vikash P. Chauhan; Margaret R. Martin; Megan E. Walsh; Matthew D. Stuber; Donald M. McDonald; Fan Yuan; Triantafyllos Stylianopoulos; Rakesh K. Jain (Drug Delivery)
To have the desired therapeutic effect, nanomedicines and macromolecular medications must move from the site of injection to the site of action, without having adverse effects. Transvascular transport is a critical step of this navigation, as exemplified by the Enhanced Permeability and Retention (EPR) effect in solid tumors, not found in normal organs. Numerous studies have concluded that passive, diffusion- and convection-based transport predominates over active, cellular mechanisms in this effect. However, recent work using a new approach reevaluated this principle by comparing tumors with or without fixation and concluded the opposite. Here, we address the controversy generated by this new approach by reporting evidence from experimental investigations and computer simulations that separate the contributions of active and passive transport. Our findings indicate that tissue fixation reduces passive transport as well as active transport, indicating the need for new methods to distinguish the relative contributions of passive and active transport.